Bioautography of dewandaru leaf ethanol extract thin-layer chromatography against Pseudomonas aeruginosa - Lesmana, I Wayan Lolik; Yasa, I Wayan Putu Sutirta; Pranitasari, Ni Putu Oktaviani Rinika (PERHATI-KL, 2025)
Background: Ear infections are a significant health concern due to their impact on hearing function. One ear infection that frequently occurs is Chronic Suppurative Otitis Media (CSOM), which is commonly caused by Pseudomonas aeruginosa. The development of therapies using natural ingredients appears to be a promising option for treating various infectious diseases. The potential of the Dewandaru leaves (Eugenia uniflora L.) has long been recognized, and several studies have demonstrated its antibacterial properties. Dewandaru leaves extract contains several active compounds with antibacterial activity, as evidenced by various in vitro studies. Purpose: To test the antibacterial activity of flavonoids, saponins, tannins, and terpenoids from Dewandaru leaves extract against American Type Culture Collection (ATCC) strain of Pseudomonas aeruginosa, ATCC 9027, as the most common cause of CSOM. Method: Antibacterial activity was assessed using the Thin-Layer Chromatography–Bioautography (TLC–bioautography) contact method using a clear area on the TLC plate. Result: Dewandaru leaf extract showed antibacterial activity against Pseudomonas aeruginosa with a significant zone of inhibition. The phytochemical substances in the extract that exhibit antibacterial activity were flavonoids. Conclusion: Dewandaru leaves had the potential to be a natural antibacterial agent against Pseudomonas aeruginosa.